2012
DOI: 10.1002/qua.24081
|View full text |Cite
|
Sign up to set email alerts
|

Why sp2‐like nanosilicons should not form: Insight from quantum chemistry

Abstract: The odd‐electron molecular theory, which takes into account the electron correlation, has been applied for a comparative consideration of sp2 nanocarbons and their siliceous analogues. Four characteristic quantities that involve the energy misalignment, the number of effectively unpaired electrons, the squared spin value, and CC and SiSi chemical bond lengths have been suggested to classify the extent of the odd electron correlation in both families. Providing a considerable enlargement of the internuclear d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 67 publications
1
22
0
Order By: Relevance
“…Wilson suggested [88] that using the clamped-nuclei Hamiltonian instead of the full one in (1.48) to define the potential might avoid the spikes but Hunter in [86] showed why this was unlikely to be the case, and Cassam-Chenai [89] repeated the work of Czub and Wolniewicz using a clamped-nuclei electronic Hamiltonian and showed that exactly the same spiky behaviour occurred.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Wilson suggested [88] that using the clamped-nuclei Hamiltonian instead of the full one in (1.48) to define the potential might avoid the spikes but Hunter in [86] showed why this was unlikely to be the case, and Cassam-Chenai [89] repeated the work of Czub and Wolniewicz using a clamped-nuclei electronic Hamiltonian and showed that exactly the same spiky behaviour occurred.…”
Section: Discussionmentioning
confidence: 99%
“…Let us conclude that the OPT method has been also successfully applied to correct description of the resonances of the Zeeman effect in a strong magnetic field, crossed electric and magnetic fields, the resonances in molecular systems, as well as descriptions of resonant states in nuclear systems such as the resonances of the compound nucleus and the resonances arising from the collision of heavy ions (nuclei), accompanied by the electron-positron pairs production (look the details in Refs. [6,80,[83][84][85][86][87][88][89][90][91]). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Briefly summarizing, the graphene radicalization is mainly concentrated on the circumference and thus is usually well inhibited by the termination of edge atoms. As for silicene, the termination of edge atoms is not enough to inhibit its high radicalization since the latter remains still high on the atoms in basal plane [31,52,53] due to which free standing one-atom thick silicene sheet cannot exist under ambient conditions. Experimental evidence of 'silicene' is related to the hexagon-patterned monolayers of silicon atoms on either Ir(111) or Ag(111) surfaces (see review [44] and references therein) chemically bound with substrates.…”
Section: X ↔ Covalent Bonds Of Heavier Tetrels (X=si Ge and Sn)mentioning
confidence: 99%
“…Weak π-conjugation has been found in Si(111)-(2×1) surface within a linear chain structure [6][7][8], but the most typical hexagonal ring structure has never been seen. This underlies the difficulty in experimentally synthesizing the elusive freestanding form of silicene [9][10][11][12][13][14].…”
mentioning
confidence: 99%